Toxicity in Evolving Twitter Topics - Geller, Marcel (2023)
Geller, M., Vasconcelos, V. V., & Pinheiro, F. L. (2023). Toxicity in Evolving Twitter Topics. In J. Mikyška, C. de Mulatier, M. Paszynski, V. V. Krzhizhanovskaya, J. J. Dongarra, & P. M. A. Sloot (Eds.), Computational Science: Computational Science – ICCS 2023 23rd International Conference, Prague, Czech Republic, July 3–5, 2023, Proceedings, Part IV (pp. 40-54). Article Chapter 4 (Lecture Notes in Computer Science; Vol. 14076). Springer. https://doi.org/10.1007/978-3-031-36027-5_4